2011
DOI: 10.1159/000332079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cannabis Treatment on the Quality of Life, Weight and Clinical Disease Activity in Inflammatory Bowel Disease Patients: A Pilot Prospective Study

Abstract: Background and Aims: Inflammatory bowel disease (IBD) patients suffer from significant morbidity and diminished life quality. The plant cannabis is beneficial in various gastrointestinal diseases, stimulating appetite and causing weight gain. Our aims were to assess whether treatment with inhaled cannabis improves quality of life, disease activity and promotes weight gain in these patients. Methods: Patients with long-standing IBD who were prescribed cannabis treatment were included. Two quality of life questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 100 publications
(60 reference statements)
9
81
0
Order By: Relevance
“…This is consistent but slightly higher than the 10% prevalence rates previously reported in Canada and Israel. 5,6 We found that patients perceive that medical marijuana is helpful for treating abdominal pain, poor appetite, and nausea associated with IBD. Patients felt it was less helpful in treating diarrhea related to their disease.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is consistent but slightly higher than the 10% prevalence rates previously reported in Canada and Israel. 5,6 We found that patients perceive that medical marijuana is helpful for treating abdominal pain, poor appetite, and nausea associated with IBD. Patients felt it was less helpful in treating diarrhea related to their disease.…”
Section: Discussionmentioning
confidence: 88%
“…An Israeli study found that 10% of patients with IBD were using recreational drugs for disease-related purposes, the majority of which was cannabis. 5 Similarly, a Canadian study found that 11.4% of patients with IBD had used cannabis in the previous year and 43.9% had used it at some point in their lifetime. 6 Patients with IBD were primarily using cannabis to alleviate abdominal pain.…”
mentioning
confidence: 97%
“…This was accompanied by an improvement in the disease activity index, perception of general health status, and ability to perform daily activities [42]. …”
Section: Human Datamentioning
confidence: 99%
“…Cannabis/Cannabinoids in IBD The inflamed gut is highly amenable to treatment with cannabinoids, which is documented for human IBD not only by anecdotal reports but, importantly, also by several questionnaire studies [70][71][72][73] as well as observational studies and prospective clinical trials [74][75][76][77]. Many of the questionnaires have revealed that patients with IBD frequently self-medicate with Cannabis to alleviate abdominal pain and diarrhea.…”
Section: Are Cannabinoids a Therapeutic Option For Inflammation And Nmentioning
confidence: 99%